Congenital nevus spilus and sun exposure. - Milano, A. (European Journal of Pediatric Dermatology, 2020)
Nevus spilus is an area of skin in which nevi more easily arise: the latter can be congenital and precede the dark background patch or acquired and be superimposed on the patch. The dark patch in most cases corresponds to lentiginous melanocyte hyperplasia with globular pattern at dermoscopy; more rarely it presents only an excess of melanin. Nevus spilus and congenital melanocytic nevus can be very similar and share clinical features. This case underlines how the sun exposure of the portion of the thigh not covered by the disposable diaper was responsible for the hyperpigmentation of the background dark patch, but not for the appearance of new nevi, since the latter were only noticeable in the portion of nevus spilus not exposed to the sun. The appearance of melanocytic neoplasms in nevus pilus is rather due to the presence of an activating somatic mutation of HRAS (2).